IMPROVING STUDENTS’ EDUCATIONAL ACTIVITIES THROUGH CASE STUDIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article is devoted to the content of problematic teaching, the teacher's lesson the ability to create problem situations in the processes and intellectual student psychological and pedagogical ways of organizing education. The main stages of teaching on the basis of problem-based education goals are indicated.